Social media mining and social network analysis emerging research - Xu, Guandong; Li, Lin (Premier reference source, 2013)
"This book highlights the advancements made in social network analysis and social web mining and their influence in the fields of computer science, information systems, sociology, organization science discipline and much more" - Provided by publisher